Evaluation of Ground Water Quality of Kathmandu Valley and Antibiotic Susceptibility test against Klebsiella pneumoniae - Ghartimagar, Samita; Khatri, Puja; Neupane, Swekshya; Joshi, Dev Raj; Joshi, Tista Prasai (Tribhuvan University Journal of Microbiology, 2020)
Objectives: The aim of this study was to assess quality status of ground water in Kathmandu valley and describe the antibiotic susceptibility of the isolated Klebsiella pneumoniae. Methods: A total of 100 samples were collected from different places of Kathmandu valley with 50 each from two different groundwater sources namely boring and well. This study was conducted from June to September, 2019 at Environment and Climate Study Laboratory, Nepal Academy of Science and Technology (NAST). The physicochemical analysis of the samples was done according to standard methodology. Membrane filtration technique was performed for the enumeration of total coliform and different biochemical tests were performed for isolation and identification of Klebsiella pneumoniae followed by Kirby-Bauer disc diffusion method for antibiotic susceptibility test. Results: This study reveals the poor microbiological aspects of ground water sources as 98% of total water samples crossed the standard value for total coliform count. The pH, turbidity, ammonia, nitrate and iron content were found to be higher than Nepal Drinking Water Quality Standard (NDWQS 2005) in 15%, 26%, 34%, 7% and 26% of total water samples respectively. The chloride and arsenic content in all the water samples were within the NDWQS, 2005. The 12 out of 18 isolates of Klebsiella pneumoniae from ground water source were highly resistant against first generation Cefazolin however, 15 out of 18 isolates were sensitive to Chloramphenicol. Additionally, four isolates showed zone of inhibition in intermediate range provided by Clinical and Laboratory Standard Institute (CLSI) guideline towards Imipenem and Meropenem. Conclusion: This study concludes that ground water sources were heavily contaminated by coliform bacteria and most of the physicochemical aspects were under standard limit. Although Klebsiella pneumoniae isolated from ground water were not multidrug resistant, one isolate was recorded to be resistant to Meropenem. These results alarm for circulation of antibiotic resistance in environmental bacterial isolates. Therefore, the appropriate water purification methods should be applied before consumption and should be examined periodically.